Hip Hop and the Public Sphere: Political Commitment and Communicative Practices on the Norwegian Hip Hop Scene - Nærland, Torgeir Uberg (Javnost-The Public, 2014)
In terms of its booming popularity and public outreach, lyrical thematisations of society and adherence to politicised tradition, hip hop as a form of expressive culture may in significant yet largely unexplored ways enter the framework of democratic politics as laid down in Jürgen Habermas’ theory of the public sphere. Based on in-depth interviews with key actors on the Norwegian hip hop-scene, this article explores and discusses political commitment, the degree to which Norwegian rappers can be seen to draw public attention to subaltern experience, the communicative strategies typical of the scene, and how these strategies might be relevant to public discourse. Furthermore, by highlighting recent examples of the mainstream media’s reception of hip hop music, this article shows how songs, lyrics and performances specifi c to the hip hop genre have entered public discourse, and further argues that hip hop music should be seen as an integral part of democratic public sphere processes.